Position paper on time and event-triggered communication services in the context of e-manufacturing - Tovar, Eduardo (2014)
Modern factories are complex systems where advances in networking and information technologies are opening new ways towards higher efficiency. Such move is being driven by market rules with ever-increasing competition levels, in search for faster time-to-market, improved process yield, non-stop operations, flexible manufacturing and tighter supply-chain coupling. All these aims present a common requirement, i.e. a realtime flow of information, from the plant-floor up to the management, maintenance, suppliers and clients, to support accurate monitoring and control of the factory. This stresses the importance achieved by the communication infrastructure in modern manufacturing industry. This paper presents the authors view concerning the current trends in modern factory communication systems. It addresses the problems of seamlessly integrating different information flows with diverse requirements, mainly in terms of timeliness. In this aspect, the debate between event-triggered and time-triggered communication is revisited as well as the joint support for both types of traffic. Finally, a view of where factory communication systems are moving to is also presented, showing the impact of open and widely available technologies.